PENGGUNAAN METODE C4.5 UNTUK KASUS KLASIFIKASI - albert albert (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2021)
The use of data mining is very influential in everyday life. Data mining can be used for classification, prediction, association and regression. In data mining, there are many methods that can be used to process large data sets such as the C4.5 algorithm, naive Bayes, K-means and many more. The C.45 algorithm is one of the methods for classification. The C4.5 algorithm is a modified algorithm of the ID3 algorithm. There are several modifications made to the C.45 algorithm such as continuous attributes as well as missing values. The purpose of the following article is to see words that have been used by previous researchers with the C4.5 method and the results obtained for the cases discussed. The results of research conducted by previous researchers with the C4.5 method for classification cases received a fairly good accuracy value so that it can be ignored that the C4.5 method is suitable for use in classification cases.